A rare case of endometritis after caesarean section. Case report - Sergey P. Sinchikhin; Roman V. Pavlov; Irina V. Telegina; Olga I. Ashikhmina; Asemgul R. Berkalieva (IP Berlin A.V., 2022)
The article describes a rare case of endometritis after abdominal delivery. Attention is drawn to the possibility of developing ischemia and necrosis of the uterine tissue when using the Reverden suture, as well as the development of a significant local inflammatory response due to the individual reaction to the suture material used. A case of non-surgical integrated approach to the treatment of endometritis with local tissue rejection is presented. A positive outcome of organ-preserving therapy of endometritis in terms of ischemic and necrotic changes in the area of the postoperative suture on the uterus was shown. Conservative therapy included the use of a beta-lactam class carbapenem and an antimicrobial peptide complex.